2007
DOI: 10.1002/adfm.200600794
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Sol–Gel Strategy for the Synthesis of Rod‐Shaped Nanocrystalline High‐Surface‐Area Lanthanum Phosphate Powders and Nanocoatings

Abstract: Synthesis of rod‐shaped nanocrystalline lanthanum phosphate with an average length of 40 nm even after calcination at 400 °C has been realized through a room‐temperature aqueous sol–gel process. The sol is characterized by particle‐size, zeta‐potential, and viscosity measurements. Gelation of the sol is induced by ammonia. The lanthanum phosphate phase‐formation process is followed by thermal, Fourier‐transform IR, and X‐ray diffraction analysis. Transmission electron microscopy shows that the sol and gel part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 45 publications
2
48
0
Order By: Relevance
“…31,32 Some of these previous studies have shown evidences that the nanowires/nanorods retained their morphology after calcination at 400°C-1000°C, 19,20,22,25,27 indicating that these nanowires/nanorods have high thermal stability; in this way, nanorods have been synthesized having 5-50 nm in diameter and 40 nm to several micrometers in length, and whose SSA varies from 7 to 127 m 2 /g. The preparation of nanorods of rhabdophane-type Sr-doped LaPO 4 ÁnH 2 O is less demonstrated, and indeed does not appear to be works reporting the synthesis of rhabdophane phase exclusively.…”
Section: Introductionmentioning
confidence: 91%
“…31,32 Some of these previous studies have shown evidences that the nanowires/nanorods retained their morphology after calcination at 400°C-1000°C, 19,20,22,25,27 indicating that these nanowires/nanorods have high thermal stability; in this way, nanorods have been synthesized having 5-50 nm in diameter and 40 nm to several micrometers in length, and whose SSA varies from 7 to 127 m 2 /g. The preparation of nanorods of rhabdophane-type Sr-doped LaPO 4 ÁnH 2 O is less demonstrated, and indeed does not appear to be works reporting the synthesis of rhabdophane phase exclusively.…”
Section: Introductionmentioning
confidence: 91%
“…Among the lanthanides, lanthanum has been extensively examined for its unique properties [9][10][11][12][13][14]. And lanthanum have been synthesized in various compositions such as La(OH) 3 [15], LaF 3 [16], La 2 (CO 3 ) 3 [17], LaPO 4 [18][19][20], LaBO 3 [21], LaOF [22], La 2 Sn 2 O 7 [23], La 2 O 3 [24] nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave heating induces dipole rotation or ion migration which decreases the reaction time and controls nucleation [43,44]. Ultrasonication helps in uniform particle formation and also prevents aggregation [17,45]. Further, dialysis against water helps in removal of excess of dissolved salts from the solution and also prevents aggregation on aging.…”
Section: Physical Characterization Of Synthesized Lanrsmentioning
confidence: 99%
“…They are also used as components of optoelectronic materials, upconversion materials and fluorescent agents in biological imaging [11][12][13][14][15]. A wide range of preparation techniques have been developed for lanthanum based nanoparticles including non-aqueous [16], sol-gel [17,18], solvothermal [19], hydrothermal [20], sonochemical [8,9], microwave-assisted [21,22], etc. A common feature of several of these synthesis techniques is the use of toxic stabilising agents that makes them unsuitable for biomedical use.…”
Section: Introductionmentioning
confidence: 99%